Completeness of inpatient medical resume filling - Imam Rosadi; Rindiani Indah Alysia (Rifa'Institute, 2022)
Medical resume is an important and basic sheet in inpatient medical records so it needs to be filled out completely because it is important in the process of patient treatment, insurance claims, compliance with accreditation standards, and legal evidence. However, in reality there are still many medical resumes that have not been filled out completely. The purpose of this study was to determine and the causes of incomplete filling of inpatient medical resumes. This study uses a literature review method that analyzes the results of six previous studies with relevant themes. Based on the results of this literature review study, it can be said that filling in inpatient medical resumes based on quantitative analysis of the six journals reviewed has not reached 100% (51.60% - 87.42%) and the dominant cause of incomplete filling is due to resource factors. human beings, besides that there are no SOPs and socialization of filling out medical resumes and limited facilities. Keywords: completeness, causes of completeness, medical resume.